Pelaksanaan PP RI No.19/2008 Sebagai Acuan Kinerja Camat pada Aspek Pemerintahan dan Pendidikan - Merry Chairina DM. Sinaga; Yusnah Melianti (Universitas Medan Area, 2015)
This study aims to determine the performance camat in the governance and education, which refers to PP RI No.19 / 2008. Researchers used descriptive method implemented in the District Percut Sei Tuan. The sample was the whole population is with 37 employees and only have a single variable: the implementation of PP RI No.19 / 2008 as a reference to the performance of district head in the governance and education in the District Percut Sei Tuan, Deli Serdang regency. Data collection techniques by observation through the observation either directly or indirectly to the subject under study. In this study the authors conducted interviews with respondents who considered berkopetensi in this study. The results showed that the performance camat in the governance and education, which refers to PP RI No.19 / 2008 can be categorized as good, such as the active role undertaken whenever a meeting / conference with employees and citizens. Often talked about the problem of improving the quality of work and education, an invitation to attend the big day, receiving the proposal / opinion of the district head in the field of government development issues of education, accepted the proposal of the villagers regarding the development of education, and play an active role in. arrangements regarding the education in collaboration with third parties.